QUASI-STATIC LOCALIZED INDENTATION TESTS ON ALUMINUM HONEYCOMB SANDWICH PANEL - XIN YaJun; XIAO Bo; LIU XiaoMan; CHENG ShuLiang; LI HuiJian (Jixie qiangdu)
Quasi-static localized indentation tests were carried out to investigate the indentation mechanical properties of the aluminum honeycomb sandwich panels. The destruction process,failure behaviors and typical force-displacement curves were analyzed. The impact of surface plates thicknesses,aperture sizes,intender types and boundary conditions on the ultimate load and energy absorption capacity were studied. The results indicate that the aluminum honeycomb sandwich panels have two kinds of typical force-displacement curves,and six stages are presented: elastic stage,local destruction stage,intensify stage,entirely damage stage,compression density stage and bottom damage stage. Surface plates thickness and aperture size have certain influence on load bearing capability and energy absorption capacity. Indenter types have much influence on load bearing capability and rigidity,but little influence on the energy absorption capacity. Different boundary conditions and core thicknesses have less influence on strength and energy absorption capacity of aluminum honeycomb sandwich panels.